2023
DOI: 10.1021/acs.jmedchem.3c00322
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Ruthenium(II) Metallocompound and Olaparib Synergy for Cancer Combination Therapy

Abstract: Synergistic drug combinations can extend the use of poly(ADP-ribose) polymerase inhibitors (PARPi) such as Olaparib to BRCA-proficient tumors and overcome acquired or de novo drug resistance. To identify new synergistic combinations for PARPi, we screened a "micro-library" comprising a mix of commercially available drugs and DNA-binding ruthenium(II) polypyridyl complexes (RPCs) for Olaparib synergy in BRCAproficient triple-negative breast cancer cells. This identified three hits: the natural product Curcumin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Ru(II)-based organometallic complexes are an emerging class of potential antineoplastic drugs for the treatment of different types of cancer [ 24 29 ]. In this work, we report for the first time that two Ru(II) complexes, 1 and 2 , suppress liver CSCs by targeting NF-κB and Akt/mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Ru(II)-based organometallic complexes are an emerging class of potential antineoplastic drugs for the treatment of different types of cancer [ 24 29 ]. In this work, we report for the first time that two Ru(II) complexes, 1 and 2 , suppress liver CSCs by targeting NF-κB and Akt/mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…14–18 Ru( ii ) polypyridyl complexes are known DNA and RNA targeting agents, but biological profiling of such complexes has only recently been appreciated and studied in some detail. 19–28 Hence, the pursuit of Ru( ii ) polypyridyl complexes as cellular imaging agents and potential theranostics is gathering pace with the recent progression of the thiophane containing TLD1433 to a phase II study for treating non-muscle invasive bladder cancer – the first ruthenium polypridyl based PDT agent to progress to clinical trials. 29 Ru( ii ) polypyridyl complexes exhibit many advantageous biological properties including DNA binding, ligand exchange potential, solubility, lipophilicity, charge, and importantly, useful photophysical properties that have all driven an explosion of interest in this class of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…56 To overcome these deficiencies, Gill and Ahmad recently demonstrated that the synergistic combinations of ruthenium-(II)−rhenium(I) polypyridyl metallomacrocycles with Olaparib could enhance DNA damage and resultant apoptosis. 57 However, unfortunately, a multicomponent drug mixture may cause other side effects due to complicated pharmacokinetics and unpredictable drug−drug interactions. As a result, a combination of Ru/Ir coordination units with bioactive PARP-1 inhibitors to generate a single-component agent is of great significance to promote the anticancer efficiency of the resulting Ru/Ir compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, PARP-1-mediated DNA repair pathway can restrict the anticancer efficacy of these complexes, which not only decreases the activity of the anticancer agents but also develops drug resistance . To overcome these deficiencies, Gill and Ahmad recently demonstrated that the synergistic combinations of ruthenium­(II)–rhenium­(I) polypyridyl metallomacrocycles with Olaparib could enhance DNA damage and resultant apoptosis . However, unfortunately, a multicomponent drug mixture may cause other side effects due to complicated pharmacokinetics and unpredictable drug–drug interactions.…”
Section: Introductionmentioning
confidence: 99%